Stealth optimized fisheye state routing in mobile ad-hoc networks using directional antennas - Grilo, A.; Macedo, M.; Sebastiao, P.; Nunes, M. (2005 IEEE 61st Vehicular Technology Conference, 2005)
Research on the use of directional antennas in mobile ad-hoc networks has been mostly centered on improving spatial reuse, extending the transmission range and minimizing flooding overhead. However, directional antennas are also a suitable means to achieve low probability of detection in battlefield applications. This paper proposes mechanisms to minimize the number of hops and end-to-end delay when routing packets in a multi-hop ad-hoc network, while taking into account stealth requirements. This novel scheme is based on fisheye state routing, which is modified in order to take advantage of the extended range provided by directional antennas. The routing algorithm is coupled with a power control algorithm to guarantee a low probability of detection beyond the zone covered by the omni-directional radiation footprint of the network. The performance of the proposed scheme is evaluated through computer simulation and compared with the unmodified fisheye state routing algorithm.